Ultrasonografía doppler color en preeclampsia severa como marcador de severidad - Huamán Guerrero, Moisés (2001)
Objective.- To determine the value of the doppler ultrasonography like marker of severity in severe preeclampsia. Study method: It was carried out a prospective, longitudinal study, of cohorts, in 56 patients with clinical diagnosis of severe preeclampsia that studied gestations between 26 and 38 weeks. Results.- IUGR was in 85,7% of cases, oligohydramnios in 36%. The uric acid on the average was of 7,23 ± 1.32 (range 5,5 at 9,5), proteinuria 1,78 ± 1,16 (range 0,11 at 4,91), pressure arterial stocking of 122,8 ± 6,73 (range 114 at 134). notch of the uterine artery was observed in 64%. likewise there were abnormalities of the flow in the umbilical artery and in the uterine artery in 64%, in the art. cerebral stocking 57% and in the Index Fetal Placental in 86%. There was death perinatal in 14%. Aterosis placental in 65%. Positive correlation among the growing levels of uric acid with the increase of the Resistance Index (R1) of the umbilical artery, the same thing was observed with Index Fetal Placental. Positive correlation was observed among the growing levels of proteinuria with the increase of the Index of Resistance of the umbilical artery, uterine artery and the Index Fetal Placental. 86% of cases culminated with gestation less than 34 weeks, due to the bad evolution of the fetal maternal clinical square, in all the cases there was commitment from the flow to the study doppler, levels of uric acid and proteinuria. Conclusión.- In 70% of patient with severe preeclampsia was alteration from the flow to the study doppler. It met positive correlation between the increase of the uric acid and the proteinuria with the appearance of abnormal flow in the uterine artery and in the Index Fetal Placental. The alteration of the flow fetal placental, the same as the growing levels of the uric acid and proteinuria are markers of severity in the preeclampsia.